TAKING OVER TWITTER – BALANCING FREE SPEECH AND CONTENT MODERATION - Dan Valeriu VOINEA (Annals of the University of Craiova for Journalism, Communication and Management)
In this paper we examine the significant changes in content moderation and free speech policies at Twitter following Elon Musk's controversial $44 billion acquisition in 2022. We trace the takeover process and subsequent organizational shifts, including massive layoffs and altered content guidelines. The study explores the complex balance between fostering free expression and mitigating harmful content on social media platforms, contextualizing Twitter's challenges within broader debates on digital governance and online discourse. The research analyzes Twitter's pre- and post-acquisition approaches to content moderation, highlighting Musk's "free speech absolutist" stance and its implications. Key policy changes are discussed, including reduced content removal, the "Freedom of Speech, not Freedom of Reach" principle, and expansion of user-driven moderation tools like Community Notes. The paper also addresses concerns raised by critics, advertisers, and governments regarding potential increases in misinformation and harassment under the new regime. Ultimately, this analysis underscores the ongoing tensions between free speech advocacy and responsible platform management in the digital age. It offers insights into the evolving landscape of social media governance and its wider societal impacts, particularly in light of Musk's influential role at Twitter.